GUARANTEES OF INDEPENDENCE OF LAWYER ACTIVITIES IN CENTRAL ASIAN COUNTRIES ON THE EXAMPLE OF KAZAKHSTAN AND UZBEKISTAN (Journal of actual problems of jurisprudence, 2024)
The article analyzes international standards regarding the provision of advocacy independence in the Republic of Kazakhstan and the Republic of Uzbekistan. Current issues faced by lawyers in these countries, such as access to legally protected confidentiality and the right to participate in procedural actions, are examined. The author suggests that lawyers should have the ability to access legally protected confidentiality in both criminal and civil proceedings. The necessity of introducing amendments to reduce the time frame for responding to legal inquiries is discussed to improve lawyers' access to necessary materials. Attention is also drawn to the importance of establishing guarantees for the protection of lawyers' rights during their professional activities, which is essential for the effective fulfillment of their duties. As a result of the research, theoretical conclusions and findings are presented, highlighting the importance of advocacy independence for ensuring the rule of law and protecting citizens' rights. The authors emphasize the need to strengthen the independence of lawyers and lawyers' associations in Central Asia, which corresponds to the recommendations of the International Commission of Lawyers (ICL). They note the importance of adopting effective legal and practical measures to ensure the ability of lawyers to perform their professional duties without undue influence. The article also deals with legislative norms regulating the right of lawyers to receive information, including state, commercial and other confidential information protected by law. The authors analyze the main principles of lawyer activity, including the independence of the lawyer and observance of professional ethics, enshrined in the legislation of the Republic of Uzbekistan. In conclusion, the article emphasizes the importance of international legal standards and the independence of lawyers as an integral element of the human rights protection system.Keywords: lawyer, legal confidentiality, procedural independence, rights protection, lawyer immunity, participation in court proceedings, international standards.